Edraianthus canescens (Campanulaceae), a new species from the Central Balkan peninsula - Lakušić, Dmitar; Niketić, Marjan; Rakić, Tamara; Stevanović, Vladimir (Phytotaxa, 2013)
Edraianthus canescens is described as a new species from the central part of the Balkan Peninsula (eastern Dinaric Alps of western Serbia). It is a calcicolous stenoendemic of the Ovčarsko-Kablarska gorge of the river West Morava. Its population size is estimated to be less than 2000 mature individuals occupying less than 1 km2. The new species inhabits south-facing exposed rocky crevices, rarely screes, on calcareous bedrock, at elevations between 300 and 750 m. The closest relatives are taxa distributed in the central Balkans from the Balkan-Apennine E. graminifolius complex.